Digital-Based Islamic Religious Education (PAI) Learning at the Elementary Madrasah (MI) Level (Case Study of the Development Elementary Madrasah of UIN Jakarta) - Arifin, Zaenal ‘; Indra, Hasbi; Bahruddin, E.; Handrianto, Budi (Formosa Journal of Sustainable Research, 2024)
The purpose of this study was to analyze the concept and implementation of digital-based PAI learning at MI MP UIN Jakarta, and to formulate the ideal concept of digital-based PAI learning at MI. The methodology used in this study is descriptive qualitative research by collecting data through participant observation, in-depth interviews and documentation. The results of the research on the concept of digital-based PAI learning at the MIMP UIN Jakarta level, in addition to referring to the curriculum from the Ministry of Religion and the Ministry of Education and Culture, also adopted the Habitual Curriculum, namely a character education strengthening program carried out for thirty (30) minutes before the first lesson begins every day. The implementation of digital-based PAI learning at MIMP UIN Jakarta has implemented a digitalization system in its media and learning methods with teaching materials in the form of e-teaching materials, e-modules, e-books and assessments to LMS called SmartMP. The ideal digital-based PAI learning at MI, which is implemented effectively and efficiently according to national education goals, is face-to-face learning by implementing a balance of digitalization between objectives, material standardization, methods and evaluation. These things must be integrated with the values ​​of Islamic teachings, in the affective, cognitive and psychomotor aspects which include knowledge, skills and attitudes